FINANCIAL RATIO OF APBD TO ASSESS PERFORMANCE OF BIMA CITY GOVERNMENT FINANCIAL MANAGEMENT IN 2018-2021 - Rudi Azhari; Yusril Hayadi; Surya Angga Pranata; Washimatul Bestari; Sholehatul Hasanah (Journal of Finance, Economics and Business, 2023)
Regional financial performance is measured with the aim of assessing how accountability and effectiveness of management is consistent with public service activities. The accountability assessment basically aims to determine the suitability of budget allocations with predetermined plans in accordance with the principles of effective, efficient and economical budget allocation. The research method used in this study is a descriptive quantitative method, the aim is to explain the financial performance that has been achieved by the Municipal Government of Bima based on the analysis of Financial Performance Ratios.